ASYMPTOTIC ASSESSMENT OF LOADS IN THE WIND TURBINE BLADE ATTACHMENT TO THE HUB - Bilova, Oksana (SWorld-Ger Conference proceedings, 2025)
The efficiency and durability of wind energy systems largely depend on design solutions and the reliability of their connections. One of the key elements is the contact interaction between the hub and the blade. This study examines the application of the